The influence of game duration and playing position on intensity of exercise during match-play in elite water polo players - Platanou, T.; Geladas, N. (Journal of Sports Sciences, 2006)
In this study, we assessed exercise intensity in 20 water polo games of different duration. The hypothesis that right wing players perform at a higher intensity than back and forward central players was also tested. Thirty water polo players, equally split between three field positions, participated in the study. Initially, their performance-related physiological capabilities were evaluated. Subsequently, during water polo games of short (4×7-min periods) or long duration (4×9-min periods), heart rate was monitored continuously and blood lactate concentration was measured at the end of each period. Activity patterns were also recorded using a video camera. Mean heart rate over the entire game was 156 ± 18 beats · min-1. Overall exercise intensity fluctuated around a value corresponding to the lactate threshold (4.03 ± 0.96 mmol · l-1, 86 ± 5% of peak heart rate) and decreased (P < 0.003) with game time (4.22 ± 1.8 and 3.47 ± 1.9 mmol · l-1 in the second and fourth quarter, respectively). During the last 6 min, heart rate was higher (P < 0.001) in games of short duration (156 ± 3 beats · min-1) than in games of long duration (152 ± 8 beats · min-1). Video analysis showed that the percentage of time spent in low-intensity activities (i.e. "out of game") was lower (23 vs. 26%), whereas that in high-intensity activities (i.e. "sprinting crawl") was higher (21 vs. 19%), in games of short compared with long duration. No difference was observed among players of various field positions in any of the variables examined. Thus during match-play, games of long duration produced significantly lower heart rate responses than games of short duration, and the physiological response exhibited by the players was not affected by field position. The water polo authorities should consider these results before changing game duration and coaches should prepare their athletes accordingly.